Acute Testicular Ischaemia Following Endovascular Aneurysm Repair on the Opposite Side to Intentional Internal Iliac Artery Occlusion. (2019) - Kontopodis, Nikolaos; Kafetzakis, Alexandros; Kozana, Androniki; Tzirakis, Konstantinos; Peteinarakis, Ioannis; Ioannou, Christos V.
Abstract : Introduction: Testicular ischaemia is a potential complication after endovascular aneurysm repair (EVAR), which has only rarely been reported in the literature. This is the report of a patient who presented with acute testicular ischaemia in the immediate post-EVAR period. Report: A 65 year old patient underwent EVAR for an aortic and bilateral iliac aneurysms. During the procedure, the right internal iliac artery was intentionally occluded to facilitate treatment of the common iliac aneurysm; however, the left internal iliac artery was preserved. The procedure was uneventful. On the second post-operative day the patient gradually developed symptoms of acute left testicular ischaemia. Clinical and ultrasonographic findings constituted the bases of diagnosis and the patient received conservative treatment with gradual improvement. To the authors' knowledge, this is the ninth case of testicular ischaemia after endovascular aneurysm repair reported in the literature. Conclusion: Testicular ischaemia, although rare, is a possible complication post-EVAR. Acute and chronic testicular damage found in association with an abdominal aortic aneurysm or its treatment has not been well studied in the literature and therefore may be under reported. Highlights: Acute testicular ischaemia, although rare, may occur in the immediate post-EVAR period. Changes in testicular perfusion caused by AAA and/or EVAR are not well understood and may be under-reported. Distal embolisation or inflow compromise are two possible mechanisms that may result in testicular infarction after EVAR.